2021
DOI: 10.3389/fimmu.2021.614676
|View full text |Cite
|
Sign up to set email alerts
|

Novel ELISA Protocol Links Pre-Existing SARS-CoV-2 Reactive Antibodies With Endemic Coronavirus Immunity and Age and Reveals Improved Serologic Identification of Acute COVID-19 via Multi-Parameter Detection

Abstract: The COVID-19 pandemic has drastically impacted work, economy, and way of life. Sensitive measurement of SARS-CoV-2 specific antibodies would provide new insight into pre-existing immunity, virus transmission dynamics, and the nuances of SARS-CoV-2 pathogenesis. To date, existing SARS-CoV-2 serology tests have limited utility due to insufficient reliable detection of antibody levels lower than what is typically present after several days of symptoms. To measure lower quantities of SARS-CoV-2 IgM, IgG, and IgA w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Antibodies reactive to SARS‐CoV‐2 receptor binding domain (RBD) of the spike protein and nucleocapsid protein (N‐protein) were assayed from plasma following the BU ELISA protocol as previously described. 29 Subject maternal or infant (cord/neonatal) serum or dilutions of monoclonal SARS‐CoV‐2 reactive antibodies (RBD IgG, clone CR3022, gift from the Alter lab at Ragon Institute) were added to 96‐well plates coated with the appropriate SARS‐CoV‐2 protein. The secondary antibody was anti‐human horseradish peroxidase (HRP)‐conjugated antibody against IgG (cat#A18817, Thermo Fisher, 1:2000), and detection was performed with 3,3′,5,5′‐Tetramethylbenzidine (TMB)‐ELISA substrate solution (Thermo Fisher Scientific, cat# 34029) with accompanying stop solution for TMB (Thermo Fisher Scientific, cat#N600).…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies reactive to SARS‐CoV‐2 receptor binding domain (RBD) of the spike protein and nucleocapsid protein (N‐protein) were assayed from plasma following the BU ELISA protocol as previously described. 29 Subject maternal or infant (cord/neonatal) serum or dilutions of monoclonal SARS‐CoV‐2 reactive antibodies (RBD IgG, clone CR3022, gift from the Alter lab at Ragon Institute) were added to 96‐well plates coated with the appropriate SARS‐CoV‐2 protein. The secondary antibody was anti‐human horseradish peroxidase (HRP)‐conjugated antibody against IgG (cat#A18817, Thermo Fisher, 1:2000), and detection was performed with 3,3′,5,5′‐Tetramethylbenzidine (TMB)‐ELISA substrate solution (Thermo Fisher Scientific, cat# 34029) with accompanying stop solution for TMB (Thermo Fisher Scientific, cat#N600).…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 antibody levels were quantified using a previously described enzyme-linked immunosorbent assay protocol [ 24 ]. CR3022 antibody (Abcam 273073) served as a positive control against SARS-CoV-2 receptor-binding domain (RBD).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the level of antibodies directed to RBD strongly correlates with a neutralizing response 14 , 26 , 27 , providing useful information when handling the viral particle is not possible. Furthermore, the combination of three antibody isotypes (IgG, IgA and IgM) improves the efficiency of using the test for diagnostic purposes 28 . While IgM may represent a recent infection complementing the molecular diagnosis for SARS-CoV-2 29 , a recent study showed a high incidence of IgA response in PCR + samples, even when they did not show IgM reactivity 30 .…”
Section: Discussionmentioning
confidence: 99%